Two new genera of Lathrobiina from the East Palaearctic region (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Beiträge zur Entomologie = Contributions to Entomology, 2013)
Two genera of Lathrobiina are described, illustrated, and distinguished from Lathrobium Gravenhorst, 1802 and allied genera: Elytrobium gen. n. (type species: Lathrobium monilicorne Sharp, 1889) and Sinlathrobium gen. n. (type species: Lathrobium lobrathiforme Assing, 2012). Elytrobium is distributed in the southeast of the East Palaearctic region and includes six species: E. monilicorne (Sharp, 1889), comb. n. (Japan); E. gongganum sp. n. (China: Gongga Shan); E. qinlinganum sp. n. (China: Qinling Shan); E. seminitidum sp. n. (China: Shaanxi); E. scindens sp. n. (China: Daba Shan); E. alesianum sp. n. (Taiwan). Sinlathrobium comprises four species from China: S. lobrathiforme (Assing, 2012), comb. n. (Yunnan); S. lobrathioides (Assing, 2012), comb. n. (transferred from Lathrobium) (Chongqing); S. densepunctatum sp. n. (Sichuan); S. iniquum sp. n. (Yunnan). Keys to the species of both genera are provided, and their distributions are mapped. Although all the species of both genera appear to be fully winged, four of the six Elytrobium and all the Sinlathrobium species have been recorded from only a single locality each. Three Elytrobium and three Sinlathrobium species are currently represented only by their respective holotypes. Stichwörter Coleoptera, Staphylinidae, Paederinae, Lathrobiina, Elytrobium, Sinlathrobium, Lathrobium, Lobrathium, Tetartopeus, East Palaearctic region, China, Taiwan, Japan, taxonomy, new genera, new species, new combinations, key to species, distribution maps Nomenklatorische Handlungen alesianum Assing, 2013 (Elytrobium), spec. nov. gongganum Assing, 2013 (Elytrobium), spec. nov. monilicorne (Sharp, 1889) (Elytrobium), LT; comb. nov. hitherto Lathrobium monilicorne Sharp, 1889 quinlinganum Assing, 2013 (Elytrobium), spec. nov. scindens Assing, 2013 (Elytrobium), spec. nov. seminitidum Assing, 2013 (Elytrobium), spec. nov. Elytrobium Assing, 2013 (Lathrobiina), gen. nov. Sinlathrobium Assing, 2013 (Lathrobiina), gen. noc. densepunctatum Assing, 2013 (Sinlathrobium), spec. nov. iniquum Assing, 2013 (Sinlathrobium), spec. nov. lobrathiforme (Assing, 2012) (Sinlathrobium), comb. nov. hirtherto Lathrobium lobrathiforme Assing, 2012 lobrathioides (Assing, 2012) (Sinlathrobium), comb. nov. hitherto Lathrobium lobrathioides Assing, 2012